Building plan approval and the implementation at MBKT / Muhammad Shaharuddin Ruslan - Ruslan, Muhammad Shaharuddin (Universiti Teknologi MARA, Perak, 2013)
This report is about building plan approval for three units four storey shop that owned by Ensidesa Sdn. Bhd. This report is started from the beginning process for building plan approval until the complete construction process of building. However, there are problem with this application, which is the owner do an amendment to this building. From four storey shop, they add to five storey shop without any approval from the Council. Actually, they already get the approval for building plan from the Council but they do amendment to the building. During process of building plan approval, there also a problem occur, which is they need to pay parking contribution as much as RM 90 000. But the problem occurs when the owner submit an application to reduce the parking contribution and submit a few letter of application but Council still remain the same decision for parking distribution fee. From the owner action, the building receives a notice of Stop Order and need to stop any construction work at the building. Now, the building still in appeal process to avoid it from demolishes work and it is one of illegal building at Kuala Terengganu.